PROGRAMMATIC ASSESSMENT: BAGAIMANA PENERAPANNYA? - Nadia Greviana; Dina Qurratu Ainin; Sylvia Mustika Sari; Mora Claramita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Assessment is essential in medical education as it provides an overview of the quality of students and the educational process. An urgent problem that arises regarding competence-based education is in ensuring the use of appropriate assessment approaches that provide information regarding the overall performance of students as well as feedback on students learning and provide justification for decision making according to student learning progress. Programmatic assessment is an approach that facilitates various obstacles in conventional assessment.Gaps: Programmatic assessment is a new approach that is rapidly emerging in the world of medical education globally. However, in practice, a more appropriate way is needed to introduce and implement programmatic assessment in Indonesia.Recommendation: Implementation of programmatic assessment requires the role and support from and for all stakeholders. The implementation of the five components of programmatic assessment required flexibility to adapt it to the local context, and accompanied by efforts of mentorship, promoting reflective inquiry, and providing constructive feedback in order to improve the quality of the assessment. This recommendation is expected to help medical and health professions education institutions that will implement programmatic assessment in Indonesia.